2013
DOI: 10.1096/fj.13-229781
|View full text |Cite
|
Sign up to set email alerts
|

NAD + acts on mitochondrial SirT3 to prevent axonal caspase activation and axonal degeneration

Abstract: In chronic degenerative syndromes, neuronal death occurs over long periods, during which cells progressively lose their axons and, ultimately, their cell bodies. Although apoptosis is recognized as a key event in neuronal death, the molecular mechanisms involved in CNS axons degeneration are poorly understood. Due to the highly polarized phenotypes of CNS neurons, the different neuronal subcompartments are likely to be targeted by light repetitive and localized aggression. Such locally initiated deleterious si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
12
37
0
Order By: Relevance
“…ARTICLE signalling molecules, such as the NAD þ signalling pathway, which controls axonal fate after local insults 42,43 . Similar to the findings reported here, NAD þ protects axons, but not the soma, upon global and/or local insults 19,44 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…ARTICLE signalling molecules, such as the NAD þ signalling pathway, which controls axonal fate after local insults 42,43 . Similar to the findings reported here, NAD þ protects axons, but not the soma, upon global and/or local insults 19,44 .…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our previous findings [18][19][20] , we observed that direct somatic application of rotenone, a mitochondria complex I targeting toxin, led to rapid (o4 h) and massive cell death and axonal degeneration, which was moderately but consistently reduced by BDV infection ( Supplementary Fig. 1).…”
Section: Bdv Protects From Rotenone-induced Axonal Fragmentationsupporting
confidence: 91%
See 1 more Smart Citation
“…Several groups have shown that NAD + can delay axon degeneration (4,9). Although the precise mechanisms by which NAD + delays axon degeneration are not known, a recent study suggests a possible role for SIRT3 (55). This earlier study showed that overexpression of SIRT3 delayed axon degeneration in an excitotoxic model.…”
Section: Discussionmentioning
confidence: 91%
“…58 Furthermore, axonal degeneration was prevented by NAD + via mitochondrial SIRT3 rather than SIRT1. 59 It is worth to mention that mechanisms of neuronal death and axonal degeneration often differ. For instance, the Wlds protein has no effect on survival of the neuronal soma.…”
Section: Discussionmentioning
confidence: 99%